(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT The purpose of this study was to find out and analyze how the government’s strategy in improving human resources at the Department of Transportation of North Luwu Regency. This study used descriptive qualitative with data collection techniques through interviews and observations. The results showed that the Strategy for Increasing the Competence of Human Resources at the Transportation Service of North Luwu Regency had not run well in terms of the aspect of the work plan process carried out in accordance with existing procedures in an effort to increase human resources, the organizational aspect of the North Luwu Regency Transportation Service was seen From the division of tasks given in accordance with their respective main functions, it was very influential on employee performance to be more optimal in carrying out their duties, aspects of providing motivation, namely the process of providing encouragement or work enthusiasm so that they were able to work together in an effort to achieve job satisfaction, aspects of supervision that employee measurements were carried out in supervising the work activities of the transportation agency, and comparisons such as what was done in assessing the success of monitoring the improvement of human resources. Keywords: Improvement Strategy, Competence, Human Resources